Hawking-Page transition in 4D Einstein-Gauss-Bonnet gravity - Xiao-yan Hu; Yuan-zhang Cui; Wei Xu (Nuclear Physics B)
This paper delves into the Hawking-Page phase transitions of charged Anti-de Sitter (AdS) black holes within the context of four-dimensional Einstein-Gauss-Bonnet gravity are presented. Reentrant Hawking-Page phase transition, alongside triple points are introduced in spherically symmetric charged AdS black holes. The reentrant transition is characterized by two distinct Hawking-Page transitions, each associated with unique temperatures, while the triple points signify the simultaneous existence of small, massless, and large black holes. The hyperbolic Gauss-Bonnet charged AdS black hole solution is given, establishing that both charged and uncharged hyperbolically symmetric AdS black holes manifest the classical Hawking-Page phase transition properties. P-T phase diagram are constructed under dual symmetries, highlighting special points such as triple and critical points, and analyzing how variations in the Gauss-Bonnet constant and electric potential impact Hawking-Page phase transitions. The 4D Einstein-Gauss-Bonnet gravity theory, which serves as an effective four-dimensional reduction of the Gauss-Bonnet gravitational theory, bearing immense theoretical significance. According to the AdS/CFT correspondence theory, the conventional Hawking-Page phase transition finds interpretation as the confinement-deconfinement transition within gauge theories, while the reentrant Hawking-Page phase transition and triple points can also be interpreted as the phase transition and triple points in the QCD phase diagram. These advancements hold promise for deepening insights into black hole thermodynamics in the framework of quantum gravity.